2019
DOI: 10.18203/2320-1770.ijrcog20193033
|View full text |Cite
|
Sign up to set email alerts
|

Role of multi-detector computed tomography in the detection and differentiation of adnexal mass lesions

Abstract: Background: The objective of this study was to evaluate the role of multi-detector computed tomography (MDCT) in the detection and differentiation of adnexal masses using post-operative histopathology findings as the gold standard.Methods: One hundred and forty five cases that were referred with a primary diagnosis of adnexal masses on clinical or USG examination were evaluated by MDCT in the Department of Radiodiagnosis from January 2013 to December 2013. One hundred twelve cases subsequently underwent surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This finding was comparable to study by Singhet al 33 The lesions that had benign features were most commonly described as complex cyst or solidcysticin consistency. However Khalda et al 28 have noted that cystic consistency was the most common benign adnexal masses in their study. This could be because in this study dermoid cyst was the most common benign lesion having fat, soft tissue, fluid and calcifications.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…This finding was comparable to study by Singhet al 33 The lesions that had benign features were most commonly described as complex cyst or solidcysticin consistency. However Khalda et al 28 have noted that cystic consistency was the most common benign adnexal masses in their study. This could be because in this study dermoid cyst was the most common benign lesion having fat, soft tissue, fluid and calcifications.…”
Section: Resultsmentioning
confidence: 71%
“…The finding is comparable to study of Pradhaet al 25 and Ranabhat et al 26 There was no significant difference in prevalence of masses in right or left ovary in this study. However, higher prevalence of masses in the right ovary compared to left ovary was found in a study by Bagdeet al 27 and higher prevalence was found in the left ovary by Kaldha et al 28 Adnexal abnormalities in pediatric patient though not common are not rare. In this study single case of dermoid cyst was found in pediatric group.…”
Section: Resultsmentioning
confidence: 89%